2017
DOI: 10.1186/s12888-017-1276-4
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of perceived spatial separation induced prepulse inhibition in patients with schizophrenia: relationships to symptoms and neurocognition

Abstract: BackgroundPrepulse inhibition (PPI) and attention were impaired, which may cause psychotic symptoms and (or) hinder the cognitive functions in schizophrenia. However, due to the measurement methods of PPI, findings about the relationship between PPI and clinical symptoms, cognitive performances have been equivocal.MethodsSeventy-five schizophrenia patients (SZ) and 50 healthy controls (HC) were assessed in a modified acoustic PPI paradigm, named perceived spatial separation-induced PPI (PSS-PPI), compared to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
(59 reference statements)
1
18
0
6
Order By: Relevance
“…Electrode resistances were <5 kΩ. The eyeblink component of the acoustic startle system was measured using a human EMG startle reflex system (EMG XEYE human startle reflex, Tianminghongyuan Instruments, Beijing, China) 38 . EMG activity was band-pass filtered (10–500 Hz) and amplified by 40,000.…”
Section: Methodsmentioning
confidence: 99%
“…Electrode resistances were <5 kΩ. The eyeblink component of the acoustic startle system was measured using a human EMG startle reflex system (EMG XEYE human startle reflex, Tianminghongyuan Instruments, Beijing, China) 38 . EMG activity was band-pass filtered (10–500 Hz) and amplified by 40,000.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies that focus on the relationship between PPI and cognition in both patients with schizophrenia and healthy people have inconsistent results. PPI deficits were reported to be correlated with attention scores, working memory, verbal learning, and memory performances in both patient and control groups (Greenwood et al, ; Yang et al, ). In the recent Consortium of Genomics in Schizophrenia (COGS) study, it was reported that patients with schizophrenia with a higher PPI also had better working memory performances compared with those with a low PPI (Swerdlow et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We described the detailed measurement procedures in our other published articles (Fig. 1 ) [ 24 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Trials in each block were presented randomly with the inter-trial interval about 20 s. Note: RNRP (RNLP): right leading masking with prepulse co-location (separation); LNLP (LNRP): left leading masking with prepulse co-location (separation). We have published this paradigm in our privous paper ([ 24 ]) …”
Section: Methodsmentioning
confidence: 99%